2015
DOI: 10.1158/1535-7163.targ-15-a118
|View full text |Cite
|
Sign up to set email alerts
|

Abstract A118: PIKHER2: A phase Ib study evaluating oral BKM120 in combination with lapatinib in trastuzumab-resistant HER2-positive advanced breast cancer

Abstract: Background: Phosphatidylinositol-3-kinase (PI3K)/AKT/mammalian target of rapamycin (mTOR)-pathway is frequently activated in HER2-positive breast cancer and may play a major role in resistance to trastuzumab. Lapatinib is a dual anti-HER2/EGFR tyrosine kinase inhibitor with clinical activity after trastuzumab failure in HER2-positive advanced breast cancer (ABC). BKM120 is a pan-class I PI3K inhibitor with potent and selective activity against wild-type and mutant PI3K p110α. PIKHER2 phase Ib study aimed prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Investig. Drugs (2015) 24 (4) safe and tolerable with a recommended dose of 80 mg/day for buparlisib and 400 mg/day for sonidegib. Toxicity profile was similar to that observed in single-agent studies.…”
Section: With Investigational Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…Investig. Drugs (2015) 24 (4) safe and tolerable with a recommended dose of 80 mg/day for buparlisib and 400 mg/day for sonidegib. Toxicity profile was similar to that observed in single-agent studies.…”
Section: With Investigational Drugsmentioning
confidence: 99%
“…About 60 --70% of BCs express either or both the estrogen (ER) and the progesterone receptors [4] and about 20 --30% overexpress the HER2 oncogene [5]. Drugs that interfere with ER functions such as tamoxifen or that lower peripheral estrogen levels such as aromatase inhibitors (AIs) significantly reduce relapse and death rates when administered postsurgically in women with operable BC and to prolong progression-free and overall survival in women with advanced or metastatic BC [3,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The combination of BKM and various kinase inhibitors was also tested recently to delay tumor progression more efficiently. Some studies have shown promising results (39,40). Therefore, the discovery of escape mechanisms provides not only a potential new approach to PI3K inhibition therapy but also a novel angle to illustrate new and often surprising functional interactions between different signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…However, a phase I study of buparlisib and lapatinib that enrolled 24 patients with refractory HER2 + breast cancer reported increased toxicity with 5 patients experiencing DLTs in the first cycle of treatment. 27 No evidence was found of a PK drug–drug interaction. The recommended phase 2 dose of buparlisib was therefore reported as 80 mg daily with 1000 mg of lapatinib.…”
Section: Discussionmentioning
confidence: 99%